CHANGES IN CONSUMER LIKEABILITY LEVEL BASED ON SENSORY PARAMETERS ON STORED INTIP WITH DIFFERENCES IN TEMPERATURE AND LENGTH OF STORAGE - Lestari, Winanti Nuri; Wulandari, Yustina Wuri; Nuraini, Vivi (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Intip is a crust that usually sticks to the base of a saucepan or pot. Intip as traditional food that has existed since time immemorial makes peeping popular in some areas in Indonesia. Indonesia's diverse regional conditions, causing the need to handle the storage of peep products influenced by temperature and length of storage. The purpose of this study is to find out the level of acceptance (preference) of consumers to fried peep products stored with different temperatures and storage lengths. This study was conducted by means of peep products stored at a temperature of 25ºC, 35ºC and 45ºC and then conducted sensory testing (fondness) attributes texture, color, aroma and overall fondness on the 0, 3, 6, 9, 12, 15 and 18 to determine the level of consumer acceptance. The result of this study is intip that is stored in the span of 3 to 6 days at a temperature of 35ºC is a tip that consumers like. The level of consumer preference for intip decreased on average on the 9th to the 18th day. The overall fondness for intip during storage was intip stored at 35ºC for 6 days, with an attribute score of crunchy (3,96), color (3,14), flavour (2,86) and overall fondness (3,61). Storage at 25ºC for 18 days is a storage condition that consumers do not like with a crunchy attribute score (1,81), color (1,50), flavour (2,00) and overall  (1,35).